1976
DOI: 10.1039/p29760000993
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the hydrochloric acid-catalysed hydrolyses of benzoic anhydrides in various dioxan–water mixtures

Abstract: Kinetic studies on the hydrolysis of some benzoic anhydrides in the presence of 0.1 00M-hydrochloric acid have been performed in various dioxan-water mixtures over the temperature range 50-70 "C. The kinetic data indicate that the hydrolysis of p-methoxybenzoic anhydride proceeds by an A1 mechanism, whereas benzoic anhydride and its p-t-butyl and p-chloro-derivatives hydrolyse by an A2 mechanism in the water-rich mixtures, but a shift of the reaction mechanism towards the A1 type occurs when the water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Before designing new systems that make use of these reactions, however, it is necessary to understand the effects of changes in the substrate structure. The two individual reactions making up this system, the reactions of carbodiimides with carboxylic acids ,, and anhydride hydrolysis, have been extensively studied in organic chemistry for many decades but were typically studied separately. Thus, there is little data available that can be used directly to predict behavior in new out-of-equilibrium systems.…”
Section: Introductionmentioning
confidence: 99%
“…Before designing new systems that make use of these reactions, however, it is necessary to understand the effects of changes in the substrate structure. The two individual reactions making up this system, the reactions of carbodiimides with carboxylic acids ,, and anhydride hydrolysis, have been extensively studied in organic chemistry for many decades but were typically studied separately. Thus, there is little data available that can be used directly to predict behavior in new out-of-equilibrium systems.…”
Section: Introductionmentioning
confidence: 99%
“…Before designing new systems making use of these reactions, however, it is necessary to understand the effects of changes in substrate structure. The two individual reactions making up this system, the reactions of carbodiimides with carboxylic acids 28,29,[32][33][34][35][36][37][38][39][40][41][42][43] and anhydride hydrolysis, [44][45][46][47][48][49][50][51][52][53][54] have been extensively studied in organic chemistry for many decades, but were typically studied separately. Thus, there is little data available that can be used directly to predict behavior in new out-of-equilibrium systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the A2 mechanism, the transition state contains a water molecule whereas in the A1 mechanism it does not contain a water molecule. A1 mechanism was found to be dominant at low water concentrations and high acidity, while A2 mechanism was found to be dominant at higher water concentrations and low acidity [3 -51 and the molecular reaction mechanism to be valid at very low water concentrations [15]. However, in none of the studies on reaction mechanism a quantitative study of the transition from A2 to A1 or the molecular mechanisms is reported.…”
Section: Mechanism-based Interpretation Of Rate Datamentioning
confidence: 99%
“…Halder [6] fitted the above three rate equations to the rate data at different temperatures and concentrations of reactants, solvent and catalyst derived from transient batch reactor temperature data and the final rate equations arrived at are given below: H, = -1.72 -log (1000 C,) -0.32 (P-98) for P>98% (15) where Cs is the concentration of sulfuric acid in mol/m3 and P is the v01.-% of acetic acid.…”
Section: Mechanism-based Interpretation Of Rate Datamentioning
confidence: 99%